Implikasi Perkembangan Kognitif Afektif Psikomotorik Moral dan Spiritual Peserta Didik dalam Pembelajaran pada Sekolah Dasar Kelas 6 - Ramadhan Lubis; Aulia Rahmadani; Amelia Rika Fadillah; Fadillah Fadillah; Winda Amelia Putri; Laila Khairani Nasution; Khairunnisa Khairunnisa (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This research aims to determine the implications of the cognitive, affective, psychomotor, moral and spiritual development of grade 6 elementary school children in learning. The method used is a qualitative research method with a descriptive approach. The data collection techniques used were interviews, observation and documentation, with the research subjects being grade 6 students and grade 6 homeroom teachers located at SDIT Al-Fatih. Based on the research conducted, the results showed that the implications of cognitive development in learning include good reasoning abilities, designing crafts, memorizing short surahs and problem solving abilities. The implications of affective development in learning are, having a sense of empathy and sympathy and having a sense of responsibility, psychomotor implications in learning, namely making comics and making handicrafts. And the implications for moral and spiritual development include obeying rules, respecting teachers, being able to lead prayers and regularly carrying out sunnah fasts.